Creative communication in the socio-psychological context: driving and hindering factors of the acculturation of Ukrainian migrants - Kovaitė, Kristina; Kononets, Mariia; Vynoslavska, Olena; Šūmakaris, Paulius (Creativity Studies, 2025)
This study explores the economic acculturation of Ukrainian migrants through the lens of psychological, communicative, and contextual factors. In this study, we investigate the challenges, hindering factors and psychological drivers affecting employment and self-employment outcomes abroad. Based on 36 semi-structured interviews conducted across nine host countries. The findings reveal shared difficulties such as language barriers, bureaucratic complexity, and gender differences in adaptation experiences. While men more frequently pursued entrepreneurship, women reported greater emotional and situational barriers to employment. Successful economic integration was associated with internal factors such as motivation, perseverance, and communication skills, alongside external supports such as family and institutional assistance. Communication and creativity emerged as key resources for resilience. The study contributes by bridging the gap between economic participation and psychological adaptation in forced migration contexts and offers a foundation for future quantitative research on migrant acculturation processes.